Magnetic and luminescent multifunctional nanohybrid: Fe3O4@CaF2:Tb3+: a facile synthesis and characterization - Vats, Monika; Kumar, Rakesh; Sharma, Jyotsna; Luwang, Meitram Niraj (Indian Journal of Pure & Applied Physics, 2020)
In the present study, bi-functional hybrid nanomaterial has been synthesized and characterized via facile method and characterized. The synthesized nanomaterial shows both magnetic and luminescent properties which are confirmed by VSM (vibrating sample magnetometer), UV-Vis spectra and the photoluminescence emission spectra. For the magnetic phase, i.e., nanocrystalline magnetite, Fe3O4 is used as the core which is then functionalized using polyethylene glycol (PEG) and for the luminescent phase, polyethylenimine (PEI) functionalized CaF2 doped with Tb3+ is used as the emitter. Wherein, both PEG and PEI serve the dual purpose of functionalization as well as stabilization by steric repulsion. The structure and morphology of the synthesized bifunctional hybrid nanomaterial are studied with the help of scanning electron microscopy (SEM) and X-ray powder diffraction.
Keywords: Biocompatible; CaF2; Co-precipitation; Fe3O4; Luminescent nanoparticle; Magnetic nanoparticles; Nanohybrid; Tb3+ doping